Modeling and Forecasting Inflation in India - Callen, Tim.; Chang, Dongkoo (Washington, D.C. : International Monetary Fund, 1999)
The Reserve Bank of India (RBI) has moved away from a broad money target toward a 'multiple indicators' approach to the conduct of monetary policy. In adopting such a framework, it is necessary to know which of the many potential indicators provide the most reliable and timely information on future developments in the target variable(s). This paper assesses which indicators provide the most useful information about future inflationary trends. It concludes that while the broad money target has been de-emphasized, developments in the monetary aggregates remain an important indicator of future inflation. The exchange rate and import prices are also relevant, particularly for inflation in the manufacturing sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet